2020
DOI: 10.1038/s41419-020-2646-2
|View full text |Cite
|
Sign up to set email alerts
|

MCL1 inhibitors S63845/MIK665 plus Navitoclax synergistically kill difficult-to-treat melanoma cells

Abstract: Current treatment for patients with metastatic melanoma include molecular-targeted therapies and immune checkpoint inhibitors. However, a subset of melanomas are difficult-to-treat. These melanomas include those without the genetic markers for targeted therapy, non-responsive to immunotherapy, and those who have relapsed or exhausted their therapeutic options. Therefore, it is necessary to understand and explore other biological processes that may provide new therapeutic approaches. One of most appealing is ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(73 citation statements)
references
References 54 publications
4
67
2
Order By: Relevance
“…We and others have shown that navitoclax plus MCL1 inhibitors can be effective to kill melanomas in vitro and in vivo [6,7]; however, in our experience, the potential toxicity was higher than ABT-199 plus MCL1 inhibitors. In our previously published study, we had to lower the drug concentrations of navitoclax and MCL1 inhibitors to minimize toxicity [6].…”
Section: Discussioncontrasting
confidence: 57%
See 4 more Smart Citations
“…We and others have shown that navitoclax plus MCL1 inhibitors can be effective to kill melanomas in vitro and in vivo [6,7]; however, in our experience, the potential toxicity was higher than ABT-199 plus MCL1 inhibitors. In our previously published study, we had to lower the drug concentrations of navitoclax and MCL1 inhibitors to minimize toxicity [6].…”
Section: Discussioncontrasting
confidence: 57%
“…We and others have shown that navitoclax plus MCL1 inhibitors can be effective to kill melanomas in vitro and in vivo [6,7]; however, in our experience, the potential toxicity was higher than ABT-199 plus MCL1 inhibitors. In our previously published study, we had to lower the drug concentrations of navitoclax and MCL1 inhibitors to minimize toxicity [6]. In comparison, the combination of ABT-199 plus an MCL1 inhibitor has been tested in pre-clinical mouse studies and is considered safe even when administered at higher concentrations than what we demonstrate in this current study (S63845: 25 mg/kg twice weekly; ABT199: 50 mg/kg 2-3 times per week).…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations